2021
DOI: 10.3389/fgene.2021.753144
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome DNA Methylation Dynamics of Sheep Preimplantation Embryo Investigated by Single-Cell DNA Methylome Sequencing

Abstract: The early stages of mammalian embryonic development involve the participation and cooperation of numerous complex processes, including nutritional, genetic, and epigenetic mechanisms. However, in embryos cultured in vitro, a developmental block occurs that affects embryo development and the efficiency of culture. Although the block period is reported to involve the transcriptional repression of maternal genes and transcriptional activation of zygotic genes, how epigenetic factors regulate developmental block i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Both paternal and maternal genomes were highly methylated at the time of fertilization, and earlier studies showed that in bovine preimplantation embryos the paternal genome underwent sharp active demethylation within only a few hours of fertilization, whereas the maternal genome underwent passive demethylation from cleavage division to the 8‐cell stage (Perillo et al, 2008). Yet, Zhang et al (2021) reported that two strong waves of methylation changes occurred, (a) demethylation at the 8‐cell to 16‐cell stage and (b) methylation at the 16‐cell to 32‐cell stage in sheep. It was also reported that the elevated concentration of metabolic stressors was associated with low blastocyst rates and abnormal embryo development (Van Hoeck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Both paternal and maternal genomes were highly methylated at the time of fertilization, and earlier studies showed that in bovine preimplantation embryos the paternal genome underwent sharp active demethylation within only a few hours of fertilization, whereas the maternal genome underwent passive demethylation from cleavage division to the 8‐cell stage (Perillo et al, 2008). Yet, Zhang et al (2021) reported that two strong waves of methylation changes occurred, (a) demethylation at the 8‐cell to 16‐cell stage and (b) methylation at the 16‐cell to 32‐cell stage in sheep. It was also reported that the elevated concentration of metabolic stressors was associated with low blastocyst rates and abnormal embryo development (Van Hoeck et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The maternal genome undergoes largely passive DNA demethylation. The dynamics of methylation changes vary with species (Zhang et al, 2021). Sequestration of DNA methyltransferases to the ooplasm, including within the subcortical maternal complex (SCMC) (see below) and associated with cytoplasmic UHRF1, and preferential association of DPPA3/Stella (which inhibits DNA methylation by inhibiting DNA methyltransferase 1 recruitment by binding UHRF1) with the maternal genome may limit de novo methylation within the maternal genome (Eckersley‐Maslin et al, 2018; Han et al, 2019).…”
Section: How Is An Embryonic Genome Formed Reprogrammed Activated And...mentioning
confidence: 99%
“…The maternal genome undergoes largely passive DNA demethylation. The dynamics of methylation changes vary with species (Zhang et al, 2021).…”
Section: Changes In Chromatin In Oocytes and Embryosmentioning
confidence: 99%
“…Other species of economic or medical research importance have also been the subjects of DNA methylome studies. [20][21][22][23] In addition, mammalian genomes have kilo-to mega-base scale regions with low average methylation levels called partially methylated regions (PMDs), 24 which are also observed in oocytes in genepoor and transcriptionally inactive regions, as shown in Figure 1B.…”
Section: Dna Me Thyl Ation 21 | Exploring the Genome-wide Dna Methyla...mentioning
confidence: 99%